2015
DOI: 10.1189/jlb.3vma0315-078r
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin skews macrophages to an anti-inflammatory, IL-10-producing activation state

Abstract: Intravenous Ig is used to treat autoimmune or autoinflammatory disorders, but the mechanism by which it exerts its immunosuppressive activity is not understood completely. To examine the impact of intravenous Ig on macrophages, we compared cytokine production by LPS-activated macrophages in the presence and absence of intravenous Ig. Intravenous Ig treatment induced robust production of IL-10 in response to LPS, relative to LPS stimulation alone, and reduced production of proinflammatory cytokines. This anti-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 47 publications
0
36
0
Order By: Relevance
“…Previous studies demonstrated that serum IL-10 levels (D'Auria et al, 1999) and the percentages of IL-10Àproducing T cells (Teraki et al, 2001) are significantly higher in BP patients after therapy with the resolution of the disease than before therapy. IVIG has been reported to induce IL-10 in various models of inflammatory disease (Kozicky et al, 2015;Ramakrishna et al, 2011). Although little is known about how IVIG affects the differentiation of IL-10Àproducing cells, our results suggest that IVIG may regulate the inflammatory responses of BP by promoting the increase of IL-10Àproducing cells.…”
Section: How Does Ivig Reduce the Pathogenic Antibodies In Vivo?mentioning
confidence: 53%
“…Previous studies demonstrated that serum IL-10 levels (D'Auria et al, 1999) and the percentages of IL-10Àproducing T cells (Teraki et al, 2001) are significantly higher in BP patients after therapy with the resolution of the disease than before therapy. IVIG has been reported to induce IL-10 in various models of inflammatory disease (Kozicky et al, 2015;Ramakrishna et al, 2011). Although little is known about how IVIG affects the differentiation of IL-10Àproducing cells, our results suggest that IVIG may regulate the inflammatory responses of BP by promoting the increase of IL-10Àproducing cells.…”
Section: How Does Ivig Reduce the Pathogenic Antibodies In Vivo?mentioning
confidence: 53%
“…IVIG has been demonstrated to modulate the functions of both innate and adaptive immune cells. Thus, IVIG suppresses the activation of various innate cells such as DCs, macrophages, and monocytes, and the secretion of inflammatory cytokines while enhancing anti- inflammatory mediators like IL-10 and IL-1RA 21,[48][49][50][51][52] . The present data demonstrate that IVIG exerts autophagy in several inflammatory innate cells like monocytes, DCs and M1 macrophages but not in the cells associated with Th2 immune response like M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have observed that the administration of intravenous immunoglobulin led macrophages to secrete increasing amounts of anti-inflammatory interleukin 10 (IL10). However, this works only if the intravenous immunoglobulin is administered 1 h after the inflammatory attack, and the effect only lasts for 24 h [10]. Thus, there is a dire need to find a more permanent solution to this uncontrolled inflammation.…”
Section: Introductionmentioning
confidence: 99%